Ralstonia solanacearum and Phytophthora parasitica promote the infection of each other by disturbing host defense response together - Liu, Xi; Wang, Hancheng; Wang, Mengru; Li, Yiting; Cai, Liuti; Yin, Junliang (Frontiers in Microbiology, 2025)
Multiple infections (multi-infection), either sequential or simultaneous, affecting a single plant or crop are now considered common in plant disease epidemics. The consequences of multi-infection have been studied from the aspects of pathogen virulence, accumulation, transmission, and epidemics, as well as genetic diversity, population structure, and evolutionary trajectory. However, the dynamic changes of host defense response during multi-infection are much unclear. In this study, Rs (Ralstonia solanacearum) and Pp (Phytophthora parasitica) were used to simulate the multi-infection and uncover the defense response changes of tobacco. Results showed that the lesion diameter of Rs+Pp was 350% higher than that of Pp and 54.2% higher than that of Rs, indicating that co-infection with Rs and Pp makes tobacco more susceptible to disease. Further analysis showed that co-infection could increase the contents of Aseorbate peroxidase (APX) and Peroxidase (POD), thus lead to the excessive accumulation of Reactive oxygen species (ROS). Meanwhile, most pathogenesis-related (PR) genes were down-regulated, revealing that the immune defense response was disturbed by co-infection and resulted in susceptibility. Our study preliminarily reveals the underlying ways that Rs and Pp co-infection suppress the host defense response, which will provide a theoretical basis for scientific, reasonable and effective tobacco disease management.